Vitamin D intake and determinants of vitamin D status during pregnancy in The Norwegian Mother, Father and Child Cohort Study - Amberntsson, Anna; Bärebring, Linnea; Winkvist, Anna; Lissner, Lauren; Meltzer, Helle Margrete; Brantsæter, Anne Lise; Papadopoulou, Eleni; Augustin, Hanna (Frontiers in Nutrition, 2023)
Background Norwegian data on vitamin D status among pregnant women indicate a moderate to high prevalence of insufficient vitamin D status (25-hydroxyvitamin D (25OHD) concentrations ≤50 nmol/L). There is a lack of population-based research on vitamin D intake and determinants of 25OHD in pregnant women from northern latitudes. The aims of this study were (1) to evaluate total vitamin D intake from both diet and supplements, (2) to investigate determinants of vitamin D status, and (3) to investigate the predicted response in vitamin D status by total vitamin D intake, in pregnant Norwegian women. Methods In total, 2,960 pregnant women from The Norwegian Environmental Biobank, a sub-study within The Norwegian Mother, Father and Child Cohort Study (MoBa), were included. Total vitamin D intake was estimated from a food frequency questionnaire in gestational week 22. Concentrations of plasma 25OHD was analyzed by automated chemiluminescent microparticle immunoassay method in gestational week 18. Candidate determinant variables of 25OHD were chosen using stepwise backward selection and investigated using multivariable linear regression. Predicted 25OHD by total vitamin D intake, overall and stratified by season and pre-pregnancy BMI, was explored using restricted cubic splines in an adjusted linear regression. Results Overall, about 61% of the women had a total vitamin D intake below the recommended intake. The main contributors to total vitamin D intake were vitamin D supplements, fish, and fortified margarine. Higher 25OHD concentrations were associated with (in descending order of the beta estimates) summer season, use of solarium, higher vitamin D intake from supplements, origin from high income country, lower pre-pregnancy BMI, higher age, higher vitamin D intake from foods, no smoking during pregnancy, higher education and energy intake. During October–May, a vitamin D intake according to the recommended intake was predicted to reach sufficient 25OHD concentrations >50 nmoL/L. Conclusion The findings from this study highlight the importance of the vitamin D intake, as one of few modifiable determinants, to reach sufficient 25OHD concentrations during months when dermal synthesis of vitamin D is absent.